Enhanced production of 3-hydroxypropionic acid from glucose via malonyl-CoA pathway by engineered Escherichia coli. (January 2016) - Cheng, Zhuan; Jiang, Jiaqi; Wu, Hui; Li, Zhimin; Ye, Qin
Highlights: 3-Hydroxypropionate can be biosynthesized by engineered E. coli efficiently from glucose. The Acc of C. glutamicum and MCR of C. aurantiacus were co-overexpressed in E. coli . The concentration of 3-HP achieved 10.08 g/L in 36 h. Abstract: In this study, production of 3-HP via malonyl-CoA was investigated by using metabolically engineered Escherichia coli carrying heterogeneous acetyl-CoA carboxylase (Acc) from Corynebacterium glutamicum and codon-optimized malonyl-CoA reductase (MCR) from Chloroflexus aurantiacus . Three engineered E. coli strains with different host-vector systems were constructed and investigated. The results indicated that the combination of E. coli BL21(DE3) and pET28a was the most efficient host-vector system for 3-HP production, and the highest concentration of 3-HP attained in shake flask cultivation reached 1.80 g/L by the strain BE-MDA with induction at 0.25 mM IPTG and 25 °C, and supplementation of NaHCO3 and biotin. In fed-batch fermentation performed in a 5-L reactor, the concentration of 3-HP achieved 10.08 g/L in 36 h.